The problem of age differentiation of university students in physical education - Volkov V.L (Kharkov National Pedagogical University, 2012)
It is considered the features of the system of physical education students in higher education at this stage. It is determined the need of introducing a mechanism of age differentiation of students in the process of physical training on the basis of analysis of local researchers. It is investigated the age-dynamics of physical development and functional capabilities of students of pedagogical professions, who are trained in basic medical group. There were statistically significant changes in the results of the study components functional training boys from 17 to 18 and from 19 to 20 years.